Regulation of mTOR and ERK Signaling in the Amygdala Through Proteolytic Modulation of PP2A Activity Following Auditory Fear Learning - (:unkn) unknown (My University, 2015)
The consolidation of fear memories is known to depend on a number of critical cellular processes including de novo protein synthesis and 26S proteasome-dependent protein degradation following auditory fear conditioning (Jarome et al., 2011; Kwapis et al., 2011). Early work has suggested that protein degradation, mediated by the ubiquitin proteasome system (UPS), may regulate the requirement for de novo protein synthesis during memory consolidation (Jarome & Helmstetter, 2014). However, the precise way in which the UPS is able to regulate mechanisms of protein synthesis remain unclear. In the present set of experiments, we investigated the role of the protein phosphatase 2A (PP2A) in mediating the interaction between the UPS and learning-induced mechanisms of protein synthesis during fear memory consolidation. Here we show that post-training administration of the PP2A inhibitor, okadaic acid (OA), has no effect on auditory fear memory consolidation in the amygdala. Interestingly, we also found that simultaneous, intra-amygdala infusions of the proteasome inhibitor, clasto-lactacystin β-lactone (BLAC), and OA can prevent the memory impairment that results from proteasome inhibition alone. However, in a final experiment we found that inhibition of PP2A and proteasome activity is not sufficient to rescue the BLAC-induced reduction of phosphorylated ERK seen 60 min after auditory fear conditioning. Together, these data suggest that PP2A may mediate the interaction between the UPS and mechanisms of learning-induced protein synthesis, outside of the ERK signaling pathway, during the consolidation of auditory fear memories in the amygdala.
Keywords: Amygdala; Consolidation; Fear; Memory; Proteasome; Protein Synthesis